MANAGEMENT OF AGRICULTURAL SECTOR DEVELOPMENT PROJECTS IN UKRAINE IN THE CONTEXT OF EUROPEAN INTEGRATION: STRATEGIC APPROACHES AND INCREASING EXPORT POTENTIAL (INNOVATIVE ECONOMY, 2025)
Buchynska T.V., Danko M.M.  MANAGEMENT OF AGRICULTURAL SECTOR DEVELOPMENT PROJECTS IN UKRAINE IN THE CONTEXT OF EUROPEAN INTEGRATION: STRATEGIC APPROACHES AND INCREASING EXPORT POTENTIALPurpose. The aim of the article is to substantiate strategic approaches to managing development projects in Ukraine's agricultural sector in the context of European integration.Methodology of research. General scientific and specialized methods were used in the study, which ensured a comprehensive approach that allowed for a comprehensive assessment of the development of Ukraine's agricultural sector in the context of European integration. The main methods included: statistical analysis – to study the dynamics of agro-food exports and imports, the formation of the foreign trade balance, and the assessment of industry development trends; methods of scientific abstraction, induction, and deduction – to formulate hypotheses about the development of Ukraine's agricultural sector, assess the cause-and-effect relationships between European integration, foreign trade activities, and the effectiveness of agricultural projects; abstract and logical – for theoretical generalization of results, systematization of project directions, and formulation of scientific conclusions; graphic – for visual demonstration of the dynamics of exports and imports and the structure of foreign trade.Findings. The study examines the current state of Ukraine's agricultural sector, its role in shaping the country's economic potential and ensuring food security. The impact of European integration processes on the development of agricultural enterprises, in particular on the expansion of foreign trade activities and the increase in export potential, is examined. The problematic aspects and challenges facing the Ukrainian agricultural sector are revealed. The dynamics of Ukraine's foreign trade in agro-food products with EU countries in 2018–2023 are analysed, the growth in the share of exports and the formation of a new strategic vector of economic cooperation are identified, confirming the integration of Ukrainian agricultural exports into the European market. Key areas for improving the efficiency of agricultural project management are identified. The practical aspects of forming a strategy for managing structural transformation projects in the agricultural sector are revealed, which ensures the socially oriented and environmentally balanced functioning of the industry, increases export potential, and integrates Ukrainian agribusiness into global agro-food chains.Originality. Further development was given to research on the rationale for strategic project directions for the European integration of Ukraine's agricultural sector. A comprehensive analysis of the development of Ukraine's agricultural sector was conducted from the perspective of European integration and increasing export potential.Practical value. The developed recommendations and project solutions can be used by entities in Ukraine's agricultural sector to boost foreign trade activity.Key words: agricultural sector, European integration, potential exports, project management, competitiveness, foreign trade, institutional infrastructure, innovative development.
Keywords: agricultural sector; European integration; potential exports; project management; competitiveness; foreign trade; institutional infrastructure; innovative development